Assessing Arrhythmia Burden After Catheter Ablation of Atrial Fibrillation Using an Implantable Loop Recorder: The ABACUS Study. (11th April 2013) - KAPA, SURAJ; EPSTEIN, ANDREW E.; CALLANS, DAVID J.; GARCIA, FERMIN C.; LIN, DAVID; BALA, RUPA; RILEY, MICHAEL P.; HUTCHINSON, MATHEW D.; GERSTENFELD, EDWARD P.; TZOU, WENDY; MARCHLINSKI, FRANCIS E.; FRANKEL, DAVID S.; et al.
Assessing Arrhythmia Burden After Ablation Introduction Arrhythmia monitoring in patients undergoing atrial fibrillation (AF) ablation is challenging. Transtelephonic monitors (TTMs) are cumbersome to use and provide limited temporal assessment. Implantable loop recorders (ILRs) may overcome these limitations. We sought to evaluate the utility of ILRs versus conventional monitoring (CM) in patients undergoing AF ablation. Methods and Results Forty‐four patients undergoing AF ablation received ILRs and CM (30‐day TTM at discharge and months 5 and 11 postablation). Over the initial 6 months, clinical decisions were made based on CM. Subjects were then randomized for the remaining 6 months to arrhythmia assessment and management by ILR versus CM. The primary endpoint was arrhythmia recurrence. The secondary endpoint was actionable clinical events (change of antiarrhythmic drugs [AADs], anticoagulation, non‐AF arrhythmia events, etc.) due to either monitoring strategy. Over the study period, 6 patients withdrew. In the first 6 months, AF recurred in 18 patients (7 noted by CM, 18 by ILR; P = 0.002). Five patients in the CM (28%) and 5 in the ILR arm (25%; P = NS) had AF recurrence during the latter 6 months. AF was falsely diagnosed frequently by ILR (730 of 1, 421 episodes; 51%). In more patients in the ILR compared with the CM arm, rate control agents (60% vs 39%, P = 0.02) and AADs (71% vs 44%, P = 0.04) were discontinued. Conclusion In AF ablation patients, ILR can detect more arrhythmias than CM. However, false detection remains a challenge. With adequate oversight, ILRs may be useful in monitoring these patients after ablation.